PENGARUH FAKTOR PEMBELAJARAN DAN PERTUMBUHAN TERHADAP PROSES BISNIS INTERNAL: STUDI PADA INSTALASI FARMASI RUMAH SAKIT DI DIY DAN JAWA TENGAH - , SATIBI; , Prof. Dr. Achmad Fudholi, DEA, Apt.,., ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Financial contribution of hospital pharmacy were 40 â 60% for hospital revenue, so there are one of the other revenue centre in hospital. But the constraint of the public hospital are limited financial for drug, on the other way for private hospital. The others constraint are: pharmacistâs managerial ability, the limited of pharmacist, one gate pharmaceutical services and clinical pharmacy wasnât implementation full. This condition might be change with performance analysis and the influence factors. Many study showed that the result of organisation performance, towarded by intangible assets. The aim are to know the influence of learning and growth toward the internal business processes in Hospital Pharmacy. The research was assosiative non eksperimental method. Questioners were the instrument in this research, which the indicators of learning and growth and internal business processes containt. The subject were the leader of hospital pharmacy departement at DIY and centre of java. Sample size were 191, with inclusion criteria: they were leader of hospital pharmacy which done 2 years minimal. The questioner tested validity and reliability before distibute for responden. The data was analyzed Structural Equation Model (SEM), with LISREL (Linear Structural Relationship) 8.54 program. The result showed that the human capital capability significant influential toward organizational capital capability (t-value 11.47). The human capital capability significant influential toward information capital readiness (t-value 1.97). The human capital capability positive influential toward internal business processes of hospital pharmacy but not significant (t-value 0.18). The Organizational capital capability significant influential toward information capital readiness (t-value 5.86). Information capital readiness significant influential toward internal business processes of hospital pharmacy (t-value 2.72). Organizational capital capability influential toward internal business processes of hospital pharmacy, but not significant (t-value 0.03).